بهینه‌سازی کدهای دودویی - پرویز قره باقری; سید حمید حاج سید جوادی; پروانه اصغری (علوم رایانش و فناوری اطلاعات, 2021)
All binary codes, even Huffman optimal code, are kind of non-optimal bit arrangement. Therefore, binary code optimization is a challenging problem. In this paper an algorithm is proposed to optimize the codes by converting any type of binary code to a specific type of Shannon-Fano code. Shannon-Fano codes are a type of coding with variable length, a state of these codes in the form of word codes in which in each word code there is only one bit "0" or one bit "1" at the beginning or end of the word code. Thus, considering this feature, we find that all binary values ​​are a special type of Shannon-Fano code, so given the frequency of the code, it is possible to replace word codes such as Huffman's code that are optimal comparing Shannon-Fano that optimizes the code arrangement. A considerable feature of this method is the positive return for each type of input data consisting of any type of bit combination, meaning that regardless of the code table, the efficiency of the algorithm will always be positive or equal to zero. Also, the proposed method can use symmetric word codes instead of Huffman word codes to creating symmetric codes, with reversibility and error resistance with two-way decoding.